Black female sexualities (Rutgers Univ. Press, 2015)
"Western culture has long regarded black female sexuality with a strange mix of fascination and condemnation, associating it with everything from desirability, hypersexuality, and liberation to vulgarity, recklessness, and disease. Yet even as their bodies and sexualities have been the subject of countless public discourses, black women's voices have been largely marginalized in these discussions. In this groundbreaking collection, feminist scholars from across the academy come together to correct this omission...illuminating black female sexual desires marked by agency and empowerment, as well as pleasure and pain, to reveal the ways black women regulate their sexual lives. The twelve original essays in Black Female Sexualities reveal the diverse ways black women perceive, experience, and represent sexuality. The contributors highlight the range of tactics that black women use to express their sexual desires and identities. Yet they do not shy away from exploring the complex ways in which black women negotiate the more traumatic aspects of sexuality and grapple with the legacy of negative stereotypes. Black Female Sexualities takes not only an interdisciplinary approach...drawing from critical race theory, sociology, and performance studies...but also an intergenerational one, in conversation with the foremothers of black feminist studies. In addition, it explores a diverse archive of representations, covering everything from blues to hip-hop, from Crash to Precious, from Sister Souljah to Edwidge Danticat. Revealing that black female sexuality is anything but a black-and-white issue, this collection demonstrates how to appreciate a whole spectrum of subjectivities, experiences, and desires. "..